2017
DOI: 10.1038/s41598-017-18266-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive role of spatially positioned tumour infiltrating lymphocytes in metastatic HER2 positive breast cancer treated with trastuzumab

Abstract: Disease outcomes of HER2+ breast cancers have dramatically changed after targeted therapies, such as trastuzumab, came to clinical practice but predictive factors for trastuzumab sensitivity and resistance are frequently unknown. Current work included metastatic breast cancer patients (n = 48), who were treated with trastuzumab and had pre-treatment tumour samples available. The tumours were immunostained for T-cell (CD3, CD8), natural killer (NK)-cell (CD56) and macrophage (CD68) markers and quantitative anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
1
31
1
Order By: Relevance
“…The proposed framework for automated quantification of TILs, computation of their abundance score, and its prognostic analysis of patient survival using OSCC histology images is the first of its kind. Even though the total number of cases involved in this study is limited ( n = 70), some other studies have reported results on smaller cohorts 51 ( n = 48) or using tissue microarrays 52 (TMAs), which contain much smaller snapshots of tumour /lymphocytes characteristics as compared to the whole slide images. Having said that, the results of this study need to be cross-validated on data from large multi-centric patient cohorts before they can be adopted in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed framework for automated quantification of TILs, computation of their abundance score, and its prognostic analysis of patient survival using OSCC histology images is the first of its kind. Even though the total number of cases involved in this study is limited ( n = 70), some other studies have reported results on smaller cohorts 51 ( n = 48) or using tissue microarrays 52 (TMAs), which contain much smaller snapshots of tumour /lymphocytes characteristics as compared to the whole slide images. Having said that, the results of this study need to be cross-validated on data from large multi-centric patient cohorts before they can be adopted in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the ER status was found associated with a differential expression of tumor infiltrating lymphocytes (TILs), raising the possibility of different immune-tumor interactions based on ER status [26][27][28]. Moreover, peripheral blood immune cells involved in antibody-dependent cell cytotoxicity (ADCC) and serum cytokines have been also associated to the trastuzumab response [29][30][31][32]. However, the association of response to NATC, as well as of disease relapse, with the ER status appears very elusive, requiring new stratification models to better identify the patients that can receive the best pharmacological benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of this study include the lack of comparative data with CD8 + T-cells. CD8 + cytotoxic T-cells are observed to target cancerous tissue and patients with high CD8 + T-cell infiltration have a significant increase in survival [ 42 ]. TALL-104, a CD8 + T-cell cell line, can be used as a future direction to study CD8 + T-cell influence on trastuzumab treated HER2 + breast cancer [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%